Analisis Masalah Terkait Obat pada Resep Pasien Diabetes Mellitus Tipe 2 di Rumah Sakit “X” Provinsi Aceh : Studi Cross-sectional Retrospektif - Zahniar, Zahniar; Khairunnisa, Khairunnisa; Wiryanto , Wiryanto (Journal of Pharmaceutical and Sciences, 2025)
Background: The complexity of treatment regimens and the simultaneous use of multiple medications increase the risk of drug-related problems (DRPs), which can affect the effectiveness, safety, and security of patient treatment. Objective: This study aims to explore and identify Drug-Related Problems in the treatment of patients with type 2 diabetes mellitus (T2DM) at Hospital “X”, Aceh Province, Pidie District, Aceh. Methods: This study is a quantitative descriptive study with a retrospective cross-sectional design of prescriptions for T2DM patients during the period of January-December 2024 at Hospital “X”, Aceh Province. Results: Analysis of 395 T2DM patient prescriptions that met the inclusion criteria identified a total of 1,275 Drug-Related Problems (DRPs) incidents. Potential MTO in category P.2 (drug safety) were the most common, accounting for 1,080 cases. The majority of these cases were attributed to inappropriate drug selection, followed by 132 incidents related to drug preparation. The high incidence of MTO was primarily due to adverse drug reactions and drug interactions, which were closely associated with inappropriate drug choices or improper drug combinations. The importance of a pharmaceutical service approach in improving patient safety and therapeutic effectiveness in the management of DMT2, especially in the prevention and management of drug-related problems (MTO). Conclusion: The most dominant DRP category identified was drug safety (P.2), primarily caused by inappropriate drug selection. Drug interactions resulting from suboptimal therapeutic combinations were the main contributing factor to MTO, with the majority classified as moderate in severity. These findings highlight the need for more active and systematic clinical pharmacy interventions in reviewing medication regimens, along with interprofessional collaboration to enhance therapeutic effectiveness, ensure patient safety, and reduce the incidence of MTO in the management of type 2 diabetes mellitus (T2DM).